An eye for a tooth: Thylacosmilus was not a marsupial “saber-tooth predator” - M. Janis, Christine; Figueirido, Borja; DeSantis, Larisa; Lautenschlager, Stephan (PeerJ, 2020)
Background Saber-toothed mammals, now all extinct, were cats or “cat-like” forms with enlarged, blade-like upper canines, proposed as specialists in taking large prey. During the last 66 Ma, the saber-tooth ecomorph has evolved convergently at least in five different mammalian lineages across both marsupials and placentals. Indeed, Thylacosmilus atrox, the so-called “marsupial saber-tooth,” is often considered as a classic example of convergence with placental saber-tooth cats such as Smilodon fatalis. However, despite its superficial similarity to saber-toothed placentals, T. atrox lacks many of the critical anatomical features related to their inferred predatory behavior—that of employing their enlarged canines in a killing head strike. Methods Here we follow a multi-proxy approach using canonical correspondence analysis of discrete traits, biomechanical models of skull function using Finite Element Analysis, and 3D dental microwear texture analysis of upper and lower postcanine teeth, to investigate the degree of evolutionary convergence between T. atrox and placental saber-tooths, including S. fatalis. Results Correspondence analysis shows that the craniodental features of T. atrox are divergent from those of placental saber-tooths. Biomechanical analyses indicate a superior ability of T. atrox to placental saber-tooths in pulling back with the canines, with the unique lateral ridge of the canines adding strength to this function. The dental microwear of T. atrox indicates a soft diet, resembling that of the meat-specializing cheetah, but its blunted gross dental wear is not indicative of shearing meat. Conclusions Our results indicate that despite its impressive canines, the “marsupial saber-tooth” was not the ecological analogue of placental saber-tooths, and likely did not use its canines to dispatch its prey. This oft-cited example of convergence requires reconsideration, and T. atrox may have had a unique type of ecology among mammals.
Keywords: Palaeobiology; Vertebrate palaeontology; Fossil; Evolution; Computational modelling; Saber-tooth ecomorphology; Dental microwear texture analysis; Finite element analysis; Canonical correspondence analysis